Comparison of Beta-2 Adrenergic Receptor Gene Polymorphisms Between Patients with Fibromyalgia Syndrome and Healthy Controls - Gözde ŞEN ÇAKIROĞLU; Sami HİZMETLİ and Yavuz SİLİĞ and; t KARADAĞ and; llah HAYTA and; u ÖZALTIN and; TAŞ and; le ZONTUL (Archives of Rheumatology, 2020)
Objectives: This study aims to compare the beta-2 adrenergic receptor (ADRB2) gene polymorphisms of patients with fibromyalgia syndrome (FMS) with those of healthy control subjects, and to investigate the possible relationship between symptoms of FMS and polymorphisms of the ADRB2 gene. Patients and methods: The study included 170 females (mean age 47.8±10.3 years; range, 21 to 75 years) diagnosed with FMS according to the 2010 American College of Rheumatology criteria and 170 healthy females (mean age 47.2±8.8 years; range, 20 to 72 years) as the control group. Several clinical symptoms of the participants related to FMS were questioned and recorded. The visual analog scale (VAS) and Fibromyalgia Impact Questionnaire (FIQ) scores of the fibromyalgia group were recorded. In both groups, the ADRB2 (rs1042717) single-nucleotide polymorphism was detected by way of a real-time polymerase chain reaction. The wild-type (Guanine/Guanine), the mutant type (Adenine/Adenine) and heterozygous type (Adenine/Guanine) were detected. The sample power was calculated considering the minor allele frequency. Results: The comparison of the ADRB2 gene polymorphism between patients with FMS and the control subjects showed that the groups were similar in terms of ADBR2 gene polymorphism and genotype (p>0.05). There was no significant difference in terms of genotype when the ADRB2 gene polymorphisms in patients with FMS were compared in terms of clinical symptoms, VAS and FIQ scores (p>0.05). Conclusion: Beta-2 adrenergic receptor (rs1042717) gene polymorphisms and genotype distribution are no different between patients with FMS and healthy individuals. ADRB2 gene polymorphisms in patients with FMS have no effect on clinical symptoms and VAS and FIQ scores. The results of the present study will light the way for future research into ADRB2 gene polymorphisms in the pathogenesis of FMS.